2020
DOI: 10.1017/sjp.2020.21
|View full text |Cite
|
Sign up to set email alerts
|

Are Positive Interventions Always Beneficial?

Abstract: Can people improve their lives by smiling more, trying to have a better posture, and by thinking about good memories? Can individuals become more successful by deliberatively engaging in positive actions and thoughts? Do people feel better by following recommendations from naïve psychology? In the present article we discuss these questions, noting that although some popular interventions thought to be universally beneficial (e.g., inductions of happiness, self-affirmation, empowerment, self-distancing) can som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 123 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…Indeed, our findings can help to shed some light on the current debate about when positive interventions are beneficial [ 63 ]. In line with a Positive Organizational Psychology perspective [ 64 , 65 ], our results revealed that our humor-based training may be useful for healthcare workers to manage work stress.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, our findings can help to shed some light on the current debate about when positive interventions are beneficial [ 63 ]. In line with a Positive Organizational Psychology perspective [ 64 , 65 ], our results revealed that our humor-based training may be useful for healthcare workers to manage work stress.…”
Section: Discussionmentioning
confidence: 97%
“…JD-R and positive psychological interventions in the workplace have been shown to be beneficial for workers' mental health [41,42], although conclusions and claims about their (in)effectiveness require more attention to contextual factors and other moderating and mediating variables [43]. To this end, the H-WORK project adopts a realist evaluation approach [44], which aims to identify mediators (i.e., working mechanisms) and contextual factors (i.e., moderators) that influence the interventions' outcomes.…”
Section: Job Demands-resources Theory and Positive Psychologymentioning
confidence: 99%
“…Brown et al, 2014;Friedman and Brown, 2018;Wong and Roy, 2018;Trask-Kerr et al, 2019). Academic authors have highlighted that POIs produce mixed results outside of clinical contexts (Bolier et al, 2013;Roll et al, 2019), that intervention effects are rarely replicable (Mongrain and Anselmo-Matthews, 2012;Khanna and Singh, 2019) or sustained (Turnes et al, 2020;van Zyl et al, 2020), that reported effect sizes are usually small (Bolier et al, 2013) and that the effectiveness of POIs are highly dependent upon contextual factors (Parks and Schueller, 2014;Wong and Roy, 2018).…”
Section: Introductionmentioning
confidence: 99%